Anti-Yugoslavism as an anti-Serbian platform for political and military cooperation between the Ustashas and communists within the Kingdom of Yugoslavia and during the war on the territory of the Independent State of Croatia - Glišin, Vanja; Despotović, Ljubiša (National interest, 2024)
The anti-Yugoslavism of the communist and Ustasha’s movements, which was one of the dominant political postulates but also a serious action platform between the two wars, has already been partially written about in our historiography. What we want to draw attention to is the fact that behind such anti-Yugoslavism, sometimes hidden and sometimes publicly, anti-Serbism was highlighted as the common denominator of the political actions of both ideological options. Although differently politically motivated and ideologically explained, in the last resort of the Ustashas and communists, anti-Yugoslavism was essentially anti-Serbian. It is precisely this relationship that we want to analyze in the first part of our work assignment, while we will, first of all, present their active and coordinated cooperation in the second part using examples during the Second World War that most often took place on the territory of the Independent State of Croatia, because Josip Broz's partisans spent most of the time of the war staying in that territory, with abundant logistical support, coordination and tolerance of all state and military formations of Pavelic's criminal regime.
Keywords: anti-Yugoslavism; anti-Serbs; Ustasha; communists; Yugoslavia; Independent State of Croatia; Second World War